Alpha rhythms in the left auditory cortex set the speed limit for speech comprehension - Yayue Gao; Jianing Fan; Na Xu; Libo Zhao; Lifang Deng; Ruolin Yang; Luyao Chen; Zhiwei Jing; Tingting Huang; Xiongfei Wang; Jing Wang; Pengfei Teng; et al. (Proceedings of the National Academy of Sciences, 2026)
Human cognition operates within distinct temporal windows spanning from very short to extremely long. Each cognitive function has its own processing speed range, beyond which performance deteriorates or even becomes impossible. Speech comprehension, as one of the most important cognitive functions in civilized societies, exemplifies this constraint: Performance declines markedly when speech rates exceed about 10 syllables per second. However, the neural mechanisms underlying this speed limit remain unclear. Here, by combining psychophysics, scalp-electroencephalography, transcranial alternating current stimulation (tACS), repetitive sensory stimulation, and stereo-electroencephalography (sEEG), we showed that the intrinsic alpha band activity determined the maximum rate of speech comprehension. In healthy participants, individual alpha frequency (IAF) precisely predicted the speech recognition rate threshold. Crucially, causally accelerating endogenous alpha rhythms via high-definition tACS and rhythmic auditory stimulation shifted this threshold, enhancing comprehension of ultrafast speech. Furthermore, sEEG recordings from the human auditory cortex revealed that this speed-limiting mechanism was locally determined: Faster alpha band activity in the left auditory cortex facilitated stronger neural entrainment to the speech envelope. These findings identify alpha band activity as a fundamental, malleable temporal bottleneck for linguistic processing, suggesting that the brain’s intrinsic sampling rate sets the physiological limit on human communication.